Intertextuality and Arthurian Women in David Lodge’s Small World (1984) - Anastasija Ropa (Baltic Journal of English Language, Literature and Culture)
The present article analyses intertextual references in David Lodge’s Small World. An Academic Romance (1984), focusing on allusions to the corpus of medieval and twentieth-century Arthuriana in the representation of women characters. An analysis of Arthurian allusions in the portrayal of women characters shows that Lodge introduces Arthurian women to his academic ‘Camelot’ in response to medieval and post-medieval literature about King Arthur and the Grail quest. In this respect, his representation of academic women in Small World is different from the way they are described in Lodge’s other academic novels, Changing Places and Nice Work. Lodge rarely recasts Arthurian women characters as his heroines with the exception of Prof Fulvia Morgana, who is modelled on the Arthurian sorceress Morgane/Morgause. Nevertheless, in Small World, women appear in the traditional roles of being the object of a ‘knight’s’ quest, such as Persse’s beloved Angelica and Swallow’s lover Joy, and wise advisors (Miss Maiden). Alternatively, women are portrayed as antagonistic or negative characters, the so-called ‘whores’ or ‘demonic temptresses’: such are Angelica’s twin sister Lily and the lusty Fulvia Morgana.